PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PD. KOPI KUDA BANDAR LAMPUNG - Andy Fitriyadi Dharmat Tilaar (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
Consumer perception of the same product or brand does not necessarily produce the samerating because not all consumers have complete knowledge of the condition of the product. Therefore,to be able to provide superior value to consumers and be able to calm competition, the company mustknow the consumer's judgment or perception of the competitor's product or brand, so that consumerpreferences can be known for prices based on consumer perception.In this research the consumer's decision to buy a product is based on the price. So from thatprice has a strong factor on the purchasing decision of a product. Related to this problem, it isnecessary to study the variables that influence it so that efforts can be made to solve the problem of thelow market share of coffee products from the PD Kopi Kuda. Then the research topic taken byresearchers is: "The Influence of Prices on Consumer Purchasing Decisions PD. Kopi Kuda BandarLampung. "The research hypothesis is that there is an effect of Price (X) on Purchasing Decisions (Y)on Kopi Kuda products in Bandar Lampung. This type of research in this paper is an evaluation of Price(X) on Purchase Decisions (Y) of Kopi Kuda ProductsDiscussion of the results of the analysis summary, the image can be interpreted that the pricehas a moderate influence of (62.2%) on the decision to purchase Kopi Kuda products and is significant